Technology-Enhanced English Learning (TEEL) for Dental Technician Students: Bridging Language and Technical Skills - Rosmayanti, Vivit (VELES Voices of English Language Education Society, 2025)
Technology-enhanced English Learning (TEEL) has been widely explored in general English instruction but remains underexamined in vocational education, particularly dental technology. Dental technology students must master specialized terminology, communicate effectively with healthcare professionals, and engage with industry-specific tools—many of which operate in English—creating a growing need for targeted language instruction. This study investigates how TEEL supports English for Specific Purposes (ESP) and Teaching English for Specific Purposes (TESP) in addressing dental technicians' specific linguistic and professional requirements. Data were collected from fifteen dental technology students enrolled in TEEL lessons at a private university in Indonesia through semi-structured interviews and classroom observations to explore this. The classroom observations focused on students participating in an English course incorporating TEEL, documenting their interactions with digital tools, engaging in lessons, and applying language skills in professional practice scenarios. Thematic analysis revealed two key findings: (1) the benefits of TEEL for dental technology students, including improved access to resources, self-paced learning, and increased motivation and engagement, and (2) challenges in integrating technology, such as limited access to digital tools and difficulties in adapting them for vocational learning. The results indicate that TEEL positively influences students’ acquisition of technical English, enhances their self-efficacy in professional communication, and facilitates real-world learning through interactive simulations. However, disparities in digital literacy and unequal access to technology hinder effective implementation. This study highlights the need for targeted interventions to improve digital literacy and ensure equitable access to technology, thereby maximizing TEEL’s impact on vocational education.